Pengaruh Kemudahan Dan Keamanan Transaksi Menggunakan Kode QR Terhadap Kepuasan Pengguna Shopeepay Pada Mahasiswa Universitas Atma Jaya Makassar - Djaja, Jessica; Tongli, Bernadeth; Tahendrika, Abner (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
The purpose of this study is to analyze the effect of ease and security of transactions using a QR Code on ShopeePay user satisfaction. This study uses quantitative methods with data collection techniques in the form of questionnaires. The population of this research is taken from Atma Jaya Makassar University students, ShopeePay users who have transacted using the QR Code as a payment method more than three times a month with a sample of 96 students. The results of this study indicate that the ease and security of transactions using a QR Code has a positive and significant effect either partially or simultaneously on ShopeePay user satisfaction.